The role of social proof in mediating the influence of content personalization and digital lifestyle on FOMO behavior on TikTok - Putu Sasmita Dewi; Nyoman Sri Subawa (Privietlab, 2026)
This study aims to analyze the role of social proof in mediating the influence of content personalization and digital lifestyle on Fear of Missing Out (FOMO) behavior among Generation Z TikTok users in Denpasar City. This research applies a quantitative methodology by obtaining data by administering questionnaires to 160 Generation Z respondents, who are active TikTok users. The sampling procedure used purposive sampling. Data processing was performed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) framework aided by SmartPLS software. The results show that content personalization and digital lifestyle have a positive and significant effect on FOMO behavior. In addition, these two variables have a positive and significant effect on social proof. The findings of this study also prove that social proof has a positive and significant effect on FOMO and is able to mediate the influence of content personalization and digital lifestyle on FOMO. These findings suggest that personalized content, high digital activity, and social validation through likes, comments, shares, and viral trends can reinforce social media users' fear of being left behind. This research reinforces the relevance of the Stimulus-Organism-Response (SOR) theory, where content personalization and digital lifestyle act as stimuli, social proof as an organism, and FOMO as a behavioral response. This study is anticipated to enrich the literature on digital consumer behavior trends, especially among Generation Z TikTok users.